BAHASA MEDIA: ANALISA SENSITIVITAS GENDER DAN KONTESTASI KEKUASAAN - Witriani Witriani (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
This paper discusses about media analysis especially on language news of the current issues in both electronic and printed media of Indonesia. Focus on the gender issues on the headline news of media, the writer analyzes various types of gender insensitivity among the media as being portraited in the titles especially for such criminal cases in which women were involved both as the victims and the doer or lawbreakers. It’s a library research, in which the writer focuses on certain cases to be analyzed and collects all related data to support the analysis. Since the object of the analysis is the title of various headlines news, the theoretical approaches here are theory of semiotic and representation. The research finds out that as being represented in the titles, some media are not quite sensitive in viewing various cases happened in the society, especially related to gender inequality. The media only focused on how to get a lot of audience attention but ignoring the effects on the readers. The bias news would essentially causes and strengthens myths which only bring such benefit to a certain interest especially the power or those who control the rule. The research also finds that the power relation between men and women in the public area  also contribute in generating  such bias  statements or news, not only on the choice of words but also on  angle and gender perspective. The bias news represents the bias society.